Viral Double-stranded RNAs from Vaccinia Virus Early or Intermediate Gene Transcripts Possess PKR Activating Function, Resulting in NF-κB Activation, When the K1 Protein Is Absent or Mutated - Willis, Kristen L. (American Society for Biochemistry and Molecular Biology, 2011)
PKR is a potent antiviral molecule that can terminate infection by inhibiting protein synthesis and stimulating NF-κB activation and apoptosis. Originally, it was thought that only intermediate and late gene transcription produced double-stranded (ds) RNA to activate PKR during vaccinia virus (VACV) infection. The VACV E3 or K3 proteins squelch this effect by binding to either dsRNA or PKR. However, in the absence of the K1 protein, VACV infection activates PKR at very early times post-infection and despite the presence of E3 and K3. These data suggest that VACV infection induces PKR activation by a currently unknown mechanism. To determine this mechanism, cells were infected with K1L-containing or -deficient VACVs. By using conditions that limited the progression of the poxvirus replication cycle, we observed that early gene transcripts activated PKR in RK13 cells, identifying a new PKR-activating mechanism of poxvirus infection. Using a similar approach for HeLa cells, intermediate gene transcription was sufficient to activate PKR. RNA isolated from infected RK13 or HeLa cells maintained PKR-activating properties only when dsRNA was present. Moreover, viral dsRNA was directly detected in infected cells either by RT-PCR or immunofluorescent microscopy. Interestingly, dsRNA levels were higher in infected cells in which the K1 protein was nonfunctional. Only K1 proteins with PKR inhibitory function prevented downstream NF-κB activation. These results reveal a new PKR activation pathway during VACV infection, in which the K1 protein reduces dsRNA levels early in VACV infection to directly inhibit PKR and several of its downstream antiviral effects, thereby enhancing virus survival.